Desarrollo de una propuesta para el tratamiento del agua empleada en el sistema de refrigeración de la empresa Iberplast S.A.S (2020)
This project aims to develop an alternative treatment for the water used in the cooling system of the company Iberplast S.A.S, based on the social and environmental responsibility that the company has with the care and proper use of natural resources. For the diagnosis stage, first an analysis of the historical data available to the company was carried out, where it was determined that parameters such as hardness, presence of iron and turbidity presented high values and outside the limits established by the company. These results were related to some problems of clogging by particles dissolved in the water that had presented the machines involved with the cooling system. Additionally, a representative diagnosis of the system was made from a micro to a macro level. With a complete diagnosis, turbidity, pH and the presence of iron were selected as key parameters, and based on this, coagulation and flocculation were proposed as the main treatment, since during these processes agglomeration and sedimentation of dissolved particles present in an aqueous medium is generated, reducing factors such as turbidity and the presence of iron, which are key to this project.